New industrial areas, old workers' solidarities: the browning of the auto industry multinationals' green field sites in Brazil. (1st April 2008) - Marco Aurelio Santana,
Abstract : This paper describes the ways in which auto workers in Southern Rio de Janeiro State in Brazil have successfully managed to build solidarity with their colleagues in the traditional locations of the auto industry in Brazil in the so-called ABC region near São Paulo, as well as in other parts of the world. This demonstrates the limitations of companies' strategies of seeking 'green field' sites in order to take advantage of low wages and introduce new working concepts such as 'lean production'. When unions are able to build effective links with workers on 'brown field' sites then these strategies can be subverted.